PERAN PT COCA COLA EUROPACIFIC PARTNERS DALAM MENGURANGI SAMPAH PLASTIK DI INDONESIA MELALUI THIS IS FORWARD - Sion, Kevin Christian; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The problem of plastic waste in Indonesia has become a major focus in efforts to prevent ecosystem damage. As one of the largest plastic waste producing countries in the world, Indonesia faces serious challenges related to plastic waste management. PT Coca-Cola Europacific Partners (CCEP) Indonesia, as part of a multinational company in the beverage sector whose products are quite popular in Indonesia, produces products made of plastic reaching millions of tons each year worldwide, thus contributing greatly to environmental pollution. For this reason, the company created the “This Is Forward” initiative as a form of corporate social responsibility for waste generated from the company’s products and as a form of compliance with regulations where the company operates, as well as pressure from other external parties. This study uses the NGO Role theory, the Multinational Corporation (MNC) level of analysis, and the Liberalism Perspective. The research method used is qualitative with a case study approach and literature study data collection techniques. Data were obtained from the company’s annual report, official plastic publication This Is Forward, government policy documents related to plastic waste management, as well as scientific articles and media news. The research results show that CCEP plays a role in realizing sustainability by addressing the problem of plastic waste through “This Is Forward” namely by building the Amandina Bumi Nusantara recycling facility, Launching r-PET bottles, Establishing the Mahija Parahita Nusantara Foundation, joining several environmental platforms and organizations, establishing partnerships and collaborations with other parties, and encouraging the government to create effective waste reduction regulations, EPR/ESR development, infrastructure development, and the use of the latest technology. The progress from the results of these activities is that 100% of Coca-Cola packaging can be recycled, the use of rPET reaches 19.6% in 2024 and the realization of the primary packaging collection rate reaches 148.6% in 2024. Keywords: Plastic Waste, This Is Forward, Coca-Cola Europacific Partners (CCEP), PET/r-PET, Packaging, and Collaboration.